Secondary metabolite (antibiotic) production by Indonesian endophytic fungi - Sebastian Margino (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
Endophytic microbes is a potentially new field for producing the promising secondary metabolite and a few people utilizing them. The purpose of this research is to find out the fungi which have an ability to produce new pathogenic eukaryote inhibiting antibiotic. The researches steps were isolation, selection based on the ability of isolates to utilize carbonsources and their inhibitory effect by bioassay test with indicator microbes such as Fusarium oxysporum f.sp. licopersicae, Bacillus subtilis and Candida albicans. Selected isolates was determined by their inhibitory effect value was more than 4.0. Paper chromatography technique was applied to analysis the character of antibiotic using many kinds of eluents. Optimization was done to increase the production and inhibitory effect of produced antibiotic. Isolation research step found 86 endophytic fungi isolates from many kinds of plants tissue from Yogyakarta. Selection results showed that 9 isolates had inhibitory effect value more than 4.0 and four isolates that were JA-2, MB-1, NGK-1 and KMD-7 higher than 5.0. Antibiotic production was influenced by carbon sources or kinds of substrates, for examples JA-2 isolate grown at PDB medium produced higher inhibitory effect to B. subtilis than Antibiotic-3 and GY; NGK-1 grown at Antibiotic-3 medium produced higher inhibitory effect to B. subtilis and C. albicans than others; MB-1 grown at Antibiotic -3 medium produced higher inhibitory effect to F. oxysporum than others. Finally isolates JA-2 and NGK-1 was chosen as selected isolates for development of new antibiotic.Key words : Secondary metabolite, endophytic fungi, Indonesia